Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $k$ be a commutative ring, and let $R,S$ be $k$-algebras. To me "$R$ is a $k$-algebra" means that $R$ is a $k$-module such that $a(rs)=(ar)s=r(as)$ for all $a\in k$ and $r,s \in R$. Let $M$ be a $(R,S)$-bimodule. I am trying to show that $M$ is a left $R \otimes_k S^{\text{op}}$-module.

Define a map $\phi \colon R \times S^{\text{op}} \to M$ given by $\phi(r,s) = (rm)s$. I believe that for me to progress with the proof this map has to have the property that $\phi (ar,s) = \phi (r, as)$ for $a \in k$. However $\phi(ar,s) = [(ar)m]s$ and $\phi(r, as) = (rm)(as)$. However I have no idea how to get that $a$ to pass to the other side of the $m$. How is this achieved? Is there implicitly a $k$-module structure on $M$?

share|cite|improve this question
When $R$ and $S$ are $k$-algebras, an $(R,S)$-bimodule is supposed to be $k$-symmetric, that is, the actions of $k$ on the left and on the right induced by restriction from those of $R$ and $S$ coincide. If it isn't, then it is not true that it is a $R\otimes_kS$-module in a sensible way: take $R=S=k=\mathbb Z[X]$ and $M=\mathbb Z$ with $R$- and $S$-module structures which are different in the way $X$ acts. – Mariano Suárez-Alvarez Aug 21 '12 at 19:22
what do you mean supposed to be? should we include $k$-symmetric structure in the hypothesis? – Paul Slevin Aug 22 '12 at 13:21
my book Rotman just claims that every $(R,S)$-bimodule $M$ is a left $R \otimes_k S$-module – Paul Slevin Aug 22 '12 at 14:33
up vote 4 down vote accepted

We assume $R$ and $S$ are unital. Hence there exists the canonical homomorphism $k \rightarrow R$. Hence by restricting the actions of $R$ on $M$ to $k$, $M$ can be a $k$-module. Similarle $M$ can be a $k$-module through $S$. We assume the both $k$-module structures on $M$ coincide.

Let $T = End_k(M)$ be the $k$-algebra of $k$-endomorphisms on $M$. For $r \in R$, we denote by $\lambda(r) \in T$ the endomorphism $x \rightarrow rx$. For $s \in S$, we denote by $\rho(s) \in T$ the endomorphism $x \rightarrow xs$.

$\lambda\colon R \rightarrow T$ and $\rho\colon S^{\text{op}} \rightarrow T$ are $k$-algebra homomorphisms.

Define a map $\phi \colon R \times S^{\text{op}} \to T$ by $\phi(r, s) = \lambda(r)\rho(s)$.

For $a \in k$, $a\lambda(r)\rho(s) = \lambda(ar)\rho(s) = \lambda(r)\rho(as)$.

Hence $a\phi (r,s) = \phi (ar, s) = \phi (r, as)$.

Hence there exists a $k$-linear map $f\colon R \otimes_k S^{\text{op}} \rightarrow T$ such that $f(r\otimes s) = \lambda(r)\rho(s)$. Since $\lambda(r)\rho(s) = \rho(s)\lambda(r)$, $f$ is a $k$-algebra homomorphism. Hence $f$ makes $M$ into a left $R \otimes_k S^{\text{op}}$-module.

share|cite|improve this answer
"we assume both $k$ module structures coincide" is this part of the hypotheses? otherwise why is it true? – Paul Slevin Aug 22 '12 at 12:04
@PaulSlevin , you need to assume this as part of the hypothesis, otherwise your claim is not true. This is what Mariano Suarez-Alvarez was saying above. – Manny Reyes Aug 22 '12 at 14:54
Thanks for clarifying. There must be a mistake in my book. – Paul Slevin Aug 22 '12 at 14:59

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.